An Evaluation of Energy and Economic Efficiency in Residential Buildings Sector: A Multi-criteria Analisys on an Italian Case Study - Campisi, Domenico; Gitto, Simone; Morea, Donato (International Journal of Energy Economics and Policy, 2018)
The aim of the paper is to evaluate by means of a multi-criteria analysis (Multi Criteria Decision Making - MCDM) the multiplicity of measures regarding energy efficiency and reduction in consumption of fossil fuels, with relative implementation of integrated renewable energy sources, for planning and renovation of single family residential buildings. The work analize the energy (thermal, electrical) consumed by a building of this type (an Italian case study), and, for the choice of the best technology to adopt for environmental heating (hot sanitary water and cooling), a MCDM model was used, which, in addition to economic evaluation, incorporates too energy efficiency, the reduction of CO2 emissions, the ease of procurement of raw material and the governative incentives available. Our results underline that the best solution concerns the installation of solar thermal panels combined with the heat pump. Keywords: energy efficiency, economic evaluation, residential buildings JEL Classifications: Q410, Q420, L940